Forced Vital Capacity (FVC) and heat stress with work fatigue in field workers at PT X - Wijayanti, Reni; Sumardiyono, Sumardiyono; Widjanarti, Maria Paskanita; Chahyadhi, Bachtiar; Suratna, Farhana Syahrotun Nisa; Fauzi, Rachmawati Prihatina; Ada, Yeremia Rante (Poltekkes Kemenkes Bandung, 2026)
Background: The rapid development of industry demands improvements in both the quality and quantity of production, which often burdens workers. Field workers, particularly at PT X, are exposed to various environmental factors that may affect pulmonary function, while heat stress significantly contributes to work fatigue. Objective: This study aimed to evaluate the relationship between forced vital capacity and heat stress with work fatigue among field workers at PT X. Methods: An analytical observational design with a cross-sectional method was employed, involving 32 field workers as research subjects. Forced vital capacity was measured using a Chestgraph Spirometer, heat stress was measured using a QuestTemp Heat Stress Monitor, and work fatigue was measured using a Reaction Timer. Data analysis was conducted using the chi-square test to determine the relationship between forced vital pulmonary capacity and heat stress with work fatigue. Results: The results showed a significant relationship between forced vital pulmonary capacity and work fatigue (p = 0.011), as well as between heat stress and work fatigue (p = 0.014). Conclusion: These findings were important as they provide an overview of workers’ physiological conditions that can influence occupational safety and productivity. It is recommended that companies routinely evaluate working conditions and workers’ health, and provide early training and heat stress management to prevent work fatigue and improve workers’ well-being.